The work of the Social Worker in the state of Espírito Santo in the context of the Covid-19 pandemic - Monteiro Dalton, Andréa; Ferraz Silva , Jeane Andréia; Pereira Gomes, Sislene; da Silva Costa, Carlos Augusto (Guará Journal, 2023)
This  article  is  the  result  of  the  Extension  Project  entitled:  “The  work of the Social Worker in Espírito Santo in the context of the Covid 19 pandemic” project carried out in partnership between Lótus and CRESS-ES. After data collection through of COFI and also,  after  holding  the  Seminar  “Professional  work  in  the  con-text of Covid 19”, we observed demands that allowed us to as-sess the need for the training course that sought to address the main question: How to face the dilution of professional work to institutional  demands, especially from  the  impacts  caused  by  the pandemic on professional attributions and skills. The work had to contribute to the process of continuing education of so-cial  workers  actives  in  the  various  socio-occupational spaces,  aiming to deepen the knowledge of the fundamentals of social work in Espirito Santo.
Keywords: Social work; Attributions and competencies; Espírito Santo and pandemic